Rediscounting, savings mobilization, and the rural banking system - Patalinghug, Epictetus E. (1987)
The paper assesses the performance of rural banks, particularly the role of discounting and savings mobilization in enhancing their viability. Evidence suggests that Philippine rural financial institution can mobilize savings as a reliable source of funds for a financial market which is becoming increasingly dependent on competition and efficiency. It notes that new policies geared towards the rural banking system will be effective if they are viewed as permanent rather than temporary.
Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics)
Includes bibliographical references (page 123).
Keywords: Banking industry -- Philippines -- Economic aspects; Philippines -- Rural conditions